First report of Pleurodema brachyops (Anura: Leptodactylidae) for Pacific islands (Seville Island, Chiriqui, Panama): Primer reporte de Pleurodema brachyops (Anura: Leptodactylidae) para las Islas del Pácifico (Isla Sevilla, Chiriquí, Panamá) - Romero, Angel; Quiroz, Michelle; González-Pinzón, Macario; Castillo-Vega, Patricia; Benítez-Montoya, C. Eliza (Revista Científica Vida Natural, 2025)
In Panama, Pleurodema brachyops is distributed in the provinces of Darién, Panama, Panamá Oeste, Coclé, Herrera, Veraguas and Chiriquí. We provide records of the new distribution located on Isla Sevilla (Chiriqui), thus being the first distributive record for this species on a Pacific island.